Covid-19 Credit Restructuring, Financial Risk and Operational Efficiency as Determinants of Rural Bank Profitability: Evidence from Solo Raya - Eko Yunianto; Wisnu Mawardi (DINASTI RESEARCH, 2026)
This study aims to analyze the effect of COVID-19-affected credit restructuring, Non-Performing Loan (NPL), operational efficiency (BOPO), and Cash Ratio (CR) on the profitability of Rural Banks (BPR) in the Solo Raya region, measured by Return on Assets (ROA) and Return on Equity (ROE). The COVID-19 pandemic prompted OJK to issue POJK No. 11/POJK.03/2020 as a credit restructuring relaxation policy. The study uses semi-annual secondary data from December 2019 to December 2022, covering 65 conventional BPRs in Solo Raya obtained from OJK's Banking Information System. The analytical method employs panel data regression with Fixed Effect Model (FEM) selected through Chow, Hausman, and Lagrange Multiplier tests. Results show that COVID-19 credit restructuring has a significant positive effect on ROA (coefficient 0.0007; p=0.0235), NPL has a significant negative effect on ROA (coefficient -0.148; p=0.0239) and ROE (coefficient -7.634; p=0.0000), BOPO negatively affects ROA (coefficient -0.1057; p=0.0000), while CR positively affects ROE (coefficient 0.860; p=0.0169). The ROA model explains 85.86% and the ROE model explains 79.34% of profitability variation. This study contributes to BPR management and OJK regulators in formulating adaptive post-pandemic credit risk management strategies.